ERROR ESTIMATION OF ORTHORECTIFICATION OF SMALL SATELLITE IMAGES BY DIFFERENTIAL SENSITIVITY ANALYSIS - Önder Halis Bettemir (Havacılık ve Uzay Teknolojileri Dergisi, 2010)
By using differential sensitivity analysis, horizontal and vertical accuracy of orthorectification of monoscopic images taken by small satellites without using Ground Control Points (GCP) is predicted. The analysis is performed by differentiating the colinearity equation of orthorectification procedure with respect to the satellite’s interior and exterior parameters, elevation obtained from digital elevation model (DEM) and satellite velocity. In addition to this, error of registered imaging time is estimated and the contribution of this error is also taken into account. Square of the differential equations with respect to parameters are multiplied by the variance covariance matrix of the parameters and horizontal uncertainty of the orthorectification is obtained by summing the results of this multiplication. Vertical uncertainty is caused by the uncertainty of DEM and the uncertainty of the horizontal position. Vertical uncertainty caused by the horizontal uncertainty is predicted by estimating a trend by generating a surface polynomial from DEM on the basis of covariance function of Hirvonen. Contribution of each error source is illustrated and the most sensitive parameter is obtained. Analysis results revealed that camera attitude and the image acquisition time are the most important parameters and special weight should be given in order to minimize the uncertainty of the orthorectification in the most efficient way.